2022
DOI: 10.7554/elife.66695
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the deepest branches of the tree of life from ancient vertically evolving genes

Abstract: Core gene phylogenies provide a window into early evolution, but different gene sets and analytical methods have yielded substantially different views of the tree of life. Trees inferred from a small set of universal core genes have typically supported a long branch separating the archaeal and bacterial domains. By contrast, recent analyses of a broader set of non-ribosomal genes have suggested that Archaea may be less divergent from Bacteria, and that estimates of inter-domain distance are inflated due to acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(112 citation statements)
references
References 114 publications
5
106
1
Order By: Relevance
“…Further, it has recently been suggested that the branch separating the primary domains of life may be shorter than in previous estimates ( Zhu et al 2019 ). However, it was subsequently shown that the reduced estimate of the Archaea/Bacteria branch length most likely results from inter-domain gene transfers and, in agreement with earlier work ( Koonin 2015b ; Hug et al 2016 ), that the longest branch in the TOL lies between Archaea and Bacteria ( Martinez-Gutierrez and Aylward 2021 ; Moody et al 2022 ) (note that these analyses did not consider extremely fast-evolving symbionts and parasites). Improved phylogenetic models, the integration of genomic data from the diversity of recently discovered taxa as well as the use of novel approaches for rooting, such as gene tree-species tree reconciliations, for example, Szöllõsi et al (2012) , David and Alm (2011) , and Szöllõsi et al (2013) (see below), will help to determine whether this branch indeed represents the deepest split in the TOL.…”
Section: The Primary Domains Of Life and Deep Roots Of The Tolsupporting
confidence: 71%
See 1 more Smart Citation
“…Further, it has recently been suggested that the branch separating the primary domains of life may be shorter than in previous estimates ( Zhu et al 2019 ). However, it was subsequently shown that the reduced estimate of the Archaea/Bacteria branch length most likely results from inter-domain gene transfers and, in agreement with earlier work ( Koonin 2015b ; Hug et al 2016 ), that the longest branch in the TOL lies between Archaea and Bacteria ( Martinez-Gutierrez and Aylward 2021 ; Moody et al 2022 ) (note that these analyses did not consider extremely fast-evolving symbionts and parasites). Improved phylogenetic models, the integration of genomic data from the diversity of recently discovered taxa as well as the use of novel approaches for rooting, such as gene tree-species tree reconciliations, for example, Szöllõsi et al (2012) , David and Alm (2011) , and Szöllõsi et al (2013) (see below), will help to determine whether this branch indeed represents the deepest split in the TOL.…”
Section: The Primary Domains Of Life and Deep Roots Of The Tolsupporting
confidence: 71%
“…These strategies include, among various others, the development of models of DNA and protein sequence evolution that better capture the processes by which molecular sequences evolve and adequately deal with sources of systematic error (i.e., nonphylogenetic signal) in sequence data: for example, see the recent development of heterotachy mixture models ( Crotty et al 2020 ). Much of our understanding of the evolutionary history of life mainly derives from analyses of multigene concatenations based on a limited set of universally conserved single-copy marker genes (see, e.g., Martinez-Gutierrez and Aylward 2021 ; Moody et al 2022 ). Elucidating ancient divergences is challenging and requires the use of metrices to assess confidence in tree topologies and bipartitions.…”
Section: How To Make Further Progressmentioning
confidence: 99%
“…A species tree of hgc + and merB + proteomes (251 proteomes in total) from the RP35 database was reconstructed based on the 27 marker genes proposed by Moody et al (2022). 27 HMM profiles were created individually based on marker gene alignments and concatenated using HMMER v3.1.…”
Section: Methodsmentioning
confidence: 99%
“…However, biological and geological processes can impair the degree to which fossil occurrences approximate the ages of cladogenetic events (Marshall 2019), as well as the overall accuracy of fossil-calibrated clocks (e.g., Budd & Mann 2020, Carruthers & Scotland 2020). While some of the limitations of node-based approaches can be overcome by using fossils to derive prior distributions for node ages (Yang & Rannala 2005), the (semi)arbitrary configuration of these calibration densities can also largely determine the results obtained (Ho & Phillips 2009, Warnock et al 2011, Brown & Smith 2018, Moody et al 2022). Furthermore, results can also be compromised by incorrect assumptions regarding the relationships between fossils and extant terminals (Lee 2009, Near et al 2005, Parham et al 2012), which are treated with absolute certainty in node dating analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 26, 2022. ; https://doi.org/10.1101/2022.08.25.505200 doi: bioRxiv preprint Warnock et al 2011, Brown & Smith 2018, Moody et al 2022. Furthermore, results can also be compromised by incorrect assumptions regarding the relationships between fossils and extant terminals (Lee 2009, Near et al 2005, Parham et al 2012, which are treated with absolute certainty in node dating analyses.…”
Section: Introductionmentioning
confidence: 99%